Filsafat Hukum Alam: Pandangan Marcus Aurelius - Muhammad, Fahmi Dzaki (Das Sollen: Jurnal Kajian Kontemporer Hukum Dan Masyarakat, 2024)
An understanding of the philosophy of natural law is essential in exploring universal moral and legal foundations. This study aims to explore the concept of natural law philosophy by highlighting the perspective of Marcus Aurelius, a philosopher and Roman emperor. Natural law philosophy offers an in-depth view of the principles of justice that not only apply to a particular society, but are also universal for all individuals. In Marcus Aurelius’ view, natural law is an inevitable moral foundation in shaping human actions and social order. This research explores the essence of natural law in the thought of Marcus Aurelius which underlines its connection with the concepts of morals and obligations. In his philosophy, natural law is not just an external rule enforced by external forces, but also an internal principle that guides individuals to act in accordance with objective justice and morality. An in-depth analysis of Marcus Aurelius’ thoughts on natural law becomes important in the context of modern law, opening a window of insight to consider the relevance and application of this philosophy in contemporary legal structures.